Pengaruh Media Sosial Terhadap Kinerja Pemasaran Usaha Perabot di Kabupaten Kampar - Miftahul Jannah; Samsurijal Hasan; Rinda Fithriyana (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
The development of digital technology has brought about a substantial change in business marketing strategies, particularly in relation to the use of social media as an effective and reasonably priced promotional tool. Small-scale furniture businesses can strategically use social media to increase product awareness, expand their market reach, and build long-lasting customer relationships. This study aims to investigate the impact of social media on the marketing initiatives of Kampar Regency furniture enterprises. The study combined a quantitative descriptive technique with a survey method by distributing questionnaires to 60 furniture industry owners. The sampling strategy was implemented through the census. The data was analyzed using basic linear regression analysis, validity tests, reliability tests, normality tests, and hypothesis testing with t-tests and F-tests. The results showed that each research tool was reliable and valid. Regression study revealed that social media significantly and favorably affected marketing performance, with a regression coefficient value of 0.678 and a significance level of 0.000 (p<0.05). Social media can explain 58.5% of the variation in marketing success, with other factors outside the research model impacting the remaining portion, according to a coefficient of determination (R2) value of 0.585. Respondents' average scores for marketing performance and social media were 4.23 and 4.15, respectively, falling into the very good range. According to these results, furniture companies' marketing performance improves with more effective usage of social media, especially when it comes to raising sales, brand awareness, customer happiness, and loyalty. Social media has thus shown itself to be a successful marketing tactic for reaching a wider audience and fostering closer ties with customers. Furniture businesses are advised to continuously improve their digital marketing competencies to strengthen their competitiveness sustainably.